(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2004)
Medical evidence is routinely required for administration of justice allover the world. It is a common perception among Indian medical professionals that lot of time and effort is required for expert testimony in the court of law in our country. Thereby, large number of professionals avoids sharing medico legal responsibilities. Hence to investigate this issue the present study was undertaken. It revealed that on average 1 hour and 45 minutes (apart from the journey time) are spent on experts’ testimony in Delhi courts. Adjournment of the case was observed amongst 33% of the cases in which the medical professionals were summoned. The present study also discusses the way and means to improve the expert testimony recording to make it more time and cost effective and expert friendly.